Religion and U.S. Foreign Policy: An interview with Dr. Carol Lee Hamrin - Hamrin, Carol Lee (Journal of Research for Christianity in China (JRCC), 2025)
Arol Lee Hamrin is an independent author, speaker and consultant for nonprofit organizations supporting the growth of China’s Third Sector. With a Ph.D. in com- parative world history, and twenty-five years as a senior Research Specialist at the Depart- ment of State, Dr. Hamrin provides a long-term perspective on the remarkable transformation underway in China. Her special expertise is analysis of the way economic dynamics drive changes in society, culture and religion, and the implications for China and the world. Dr. Ham- rin earned the Public Justice Leadership Award for outstanding public service in 2003, and the Secretary of State’s Career Achievement Award in 2000. She has taught in D.C. - area graduate schools since 1980.